RESPON TITER ANTIBODI PADA AYAM BROILER YANG DIVAKSINASI ND DAN DIBERI HERBAL REMPAH - Ni Sri Yuliani; Gerson Y.I. Sakan (Partner, 2018)
This study aims is to find the response of antibody titers in chickens vaccinated with ND and given herbal remedies. The chickens used which were one day broiler (DOC) strain of CP 707. This extract groups were given to chickens from 7 days until 28 days in three treatment groups and one control group (drinking water). Serum samples were taken from chickens aged 7, 14, and 21 days after ND vaccination, followed by serological tests. The average that of antibody titers before were giventreatmentand 7 days post vaccination showed that the highest titers and the average antibody titers after vaccination at day 14, 21 and 28 days and post were given treatment with herbs and decoction of curry leaves were decrease. ANOVA analysis revealed that all treatments had no significant effect (P> 0.05) toward the number of antibody titers in tested broiler chickens. In the treatment of herbal medicine, a combination of herbs and decoction of curry leaves, and decoction of curry leaves whichwere given to chickens showed that there were the same number of antibody titers as the control of only drinking water. But the platelet values in the treatment group were higher than control (drinking water).